Democracy on the Border. Freedom of Movement and Popular Sovereignty - Edoardo Greblo (Scienza & Politica, 2015)
The idea that the sovereignty of the nation-state has collapsed under the weight of globalization "and it is now an empty shell" has long been a conviction rooted in political and social sciences, which speak openly of an era of post-sovereignty. However, the sovereignty of the State finds an ultimate and indispensable bulwark in the defense and in the border control. But as things stand when sovereignty is «popular»? What principles the democratic state of law can appeal to practice an immigration policy which unilaterally terminate the company to strangers? The thesis proposed in the article argues that the democratic theory does not consider, in this regard, any discretionary. If «the people is an aspiration, not a fact», as Benhabib argues, the regime of border control, to be democratically legitimate, should take into account both the perspective of insiders, and that of the outsiders.